Penyuluhan Kesehatan Reproduksi Remaja melalui Kegiatan Festival Lomba Perayaan HUT RI: The Health Education on Adolescent Reproductive Health Through a Festival Competition for Indonesia's Independence Day Celebration - Asya Syifa Ahmad Al Hadi; Aryana Eka Dewandria; Indah Dwi Anggraini; Ayu Putri Nabila Qohar; Domas Nurchandra Pramudianti; Ashila Nur Aulia R (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
In 2030, Indonesia is projected to experience a 37% increase in the number of HIV-positive patients, marking an addition of approximately 13,576 cases over 11 years. East Java, particularly among the 25-49 age group, predominantly males, stands out with the highest HIV prevalence. Factors such as inadequate knowledge among adolescents about reproductive health, exposure to pornography, and parental disempowerment contribute to risky sexual behaviors. The Activity aims to enhance adolescent reproductive health awareness, reduce HIV/AIDS cases, and supports preventative efforts at SMPN 15 Surabaya, Kenjeran, Surabaya. The community service activities encompass smart quiz seminars, educational role-playing, and informational posters. A questionnaire with 15 questions serves as metric for the success of the outreach. To analyze the methods' outcomes and effectiveness Descriptive and inferential statistics are applied. The community service initiatives successfully garnered participation from 108 students out of a total of 900 at SMPN 15 Surabaya. The seminar quiz activity with ρ-value ≤ 0.05 significantly increased students' knowledge by 14%, while role-playing and poster competitions showed no significance. Hence the festival has positively contributed to students' knowledge enhancement, particularly through the smart quiz seminar.